Análisis dinámico de sistemas en el dominio tiempo-frecuencia - Castellanos León, Francisco (My University, 2008)
Análisis dinámico de sistemas en el dominio tiempo-frecuencia
Keywords: Análisis dinámico de sistemas en el dominio tiempo-frecuencia